Expressão da tristeza em camada popular urbana de Salvador, Bahia, Brasil The expression of sadness in a working class bairro in Salvador, Bahia, Brazil - Lívia Alessandra F. da Costa; Antonio Marcos Pereira (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1995)
Este artigo examina as peculiaridades da expressão da emoção em um bairro popular de Salvador, Bahia, o Nordeste de Amaralina. Focalizando nossa exploração na expressão da tristeza, tentamos construir um esquema que possibilite a compreensão de como os informantes percebem, identificam e lidam com esta emoção no curso de suas vidas cotidianas. Perseguindo este objetivo, construímos uma rede semântica que revela a existência de três agrupamentos principais de expressão emocional: um grupo "interior", um "corporal" e outro "interativo". Observamos também as superposições entre o universo da expressão emocional e o conceito de pessoa local. This paper examines the peculiarities of the expression of emotion in a poor neighborhood from Northeastern Brazil, the bairro of Nordeste de Amaralina, in Salvador, Bahia. Focusing on the expression of sadness, we built a scheme in which to understand how the informants perceive, identify, and deal with this emotion in the course of their daily lives. We attempted to reach an understanding of the wavs people in the bairro interpret sadness. In order to accomplish this goal. we built a semantic network which revealed three main clusters of emotional expression: the inner set, the bodily set, and the interactional set. We came to realize the various superpositions benween the universe of emotional expression and the local concept of person.